STRENGTHENING FOOD SECURITY THROUGH THE USE OF YARDS DURING THE COVID 19 PANDEMIC: PENGUATAN KETAHANAN PANGAN MELALUI PEMANFAATAN LAHAN PEKARANGAN PADA MASA PANDEMI COVID 19 - Fitriyani Yuliawati; Wiwi Widiastuti; Taufik Nurohman; Intan Nurcahya (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: This activity was carried out to follow up on the problems and potential that exist in Sukajaya Hamlet, Tanjungjaya Village, the results of field observations found problems during the Covid 19 pandemic regarding the remoteness of Sukajaya Village area to the shopping centers, making it difficult for people to get access to food. Objective: This activity aims to increase the knowledge and skills of the community in order to utilize the potential that exists today, namely that almost every house where the Head of the Family lives has a yard that is large enough and can be used for planting vegetables. Method: This activity was carried out through outreach activities and training on the importance of using yard land as a family living shop (planting vegetables). Partners of this activity were Paguyuban Silih Asih 1 and 2, totaling 40 people. Results: The result showed all participants experienced an increase in knowledge and skills in using home yard land. Conclusion: Partners felt very helped by this yard land utilization training. After the activities were carried out, partners felt helped in meeting their food needs and their knowledge about food security increased.